The Effect Of The Supply Of Personal Protective Equipment, Implementation Of Health Protocol, And Patient Honesty On The Safety Of Health Personnel In The Er And Infantry Room Of Pure Teguh Hospital - Linawaty Linawaty; Chrismis Novalinda Ginting; Sri Wahyuni Nasution; Ermi Girsang (CV. Inara, 2022)
Many health workers in the world have been exposed and some have even died from COVID-19, which is currently a global pandemic. This is thought to be influenced by the personal protective equipment used by health workers, the implementation of health protocols carried out by health workers, and the honesty of patients in conveying their complaints, contact, and travel history. This study aims to determine the effect of the supply of personal protective equipment, implementation of health protocols, and patient honesty on the safety of health workers in the emergency department and inpatient rooms at Murni Teguh Hospital. This type of research is quantitative. The research sample was 100 health workers working in the emergency room and the inpatient room at Murni Teguh Hospital. The results of the chi-square test showed that there was a significant relationship between PPE supply (p=0.000), implementation of health protocols (p=0.003), and patient honesty (p=0.000) on the safety of emergency room health workers and inpatient rooms at Murni Teguh Hospital. The most influential variable is the supply of personal protective equipment (Sig.0.000). It is recommended that hospitals continue to maintain a supply of personal protective equipment to support the safety of health workers in hospitals. Health workers are expected to increase awareness of the use of personal protective equipment and the implementation of health protocols.